Study of Bactericidal Properties of Mg-Doped ZnO Nanoparticles. Issue 1804 (2015) - Perez-Altamar, Melina; Marrero, Hilary; Martínez Julca, Milton; Perales Perez, Oscar
ABSTRACT: The present work focuses on the polyol-mediated synthesis of pure and Mg-doped ZnO nanoparticles. The synthesized samples were characterized via X-ray diffraction, Fourier transformed infrared spectroscopy, ultraviolet visible spectroscopy and photoluminescence techniques. The Standard Plate Count was used to assess the bactericidal properties of the nanoparticles against E. coli at 1000 ppm and 1500 ppm of concentration. The capacity of the Zn-Mg oxides to generate singlet oxygen (SO) species was also evaluated. X-ray diffraction information evidenced the formation of ZnO-wurtzite; no diffraction peaks corresponding to isolated Mg-phases were detected. The average crystallite size of the Zn-Mg oxide nanocrystals was estimated in the 6nm - 7nm range. Infrared spectroscopy measurements confirmed the formation of the oxide with a Metal-Oxygen band centered on 536 cm -1 ; other bands associated to the functional groups of polyol by product were also observed. The exciton peak of UV spectrum suggests similarity in the particle size with the dopant addition. The effect of particle composition (i.e. doping level) on the corresponding generation of SO and bactericidal capacity is presented and discussed.